FACTORS INFLUENCING INTENTION IN USING P2P LENDING WITH ATTITUDE TOWARD DEBT AS A MEDIATING VARIABLE: CASE STUDY OF GENERATION Z IN INDONESIA - Dwi Astuti, Penitaliasih
Technological developments encourage internet use and change many things, including financial behavior. P2P Lending is an example of how technology has changed a person's financial behavior. Generation Z, who were born in this technological era, is a generation with different characteristics from previous generations. Indonesia, with its large Generation Z population, is an interesting case to study. This research examines the factors that influence intentions to use P2P Lending, especially in Generation Z. This research proposes gender, education level, income, and financial literacy as independent variables, with behavior toward debt as a mediating variable. This research used an online questionnaire to collect data from 400 respondents. This research uses SEM-PLS to determine the relationship between variables as well as additional output from the difference test using Mann-Whitney and Kruskal-Wallis which is used on demographic data.